2011
DOI: 10.1186/1477-7827-9-89
|View full text |Cite
|
Sign up to set email alerts
|

Use of aromatase inhibitors to treat endometriosis-related pain symptoms: a systematic review

Abstract: This systematic review aims to assess the efficacy of aromatase inhibitors (AIs) in treating pain symptoms caused by endometriosis. A comprehensive literature search was conducted to identify all the published studies evaluating the efficacy of type II nonsteroidal aromatase inhibitors (anastrozole and letrozole) in treating endometriosis-related pain symptoms. The MEDLINE, EMBASE, PubMed, and SCOPUS databases and the Cochrane System Reviews were searched up to October 2010. This review comprises of the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 49 publications
(85 reference statements)
0
44
0
2
Order By: Relevance
“…[55][56][57] For deeply infiltrating endometriosis, aromatase inhibitors with norethindrone may work similarly without as significant hypoestrogenic effects. 58,59 Surgery Two basic surgical approaches have been used to treat chronic pelvic pain: removing pelvic organs and treating visible disease while leaving the pelvic organs in place. The use of both approaches is guided by clinical experience, because high-quality scientific data regarding the role of surgery in pelvic pain are sparse.…”
Section: Hormonal Medicationsmentioning
confidence: 99%
“…[55][56][57] For deeply infiltrating endometriosis, aromatase inhibitors with norethindrone may work similarly without as significant hypoestrogenic effects. 58,59 Surgery Two basic surgical approaches have been used to treat chronic pelvic pain: removing pelvic organs and treating visible disease while leaving the pelvic organs in place. The use of both approaches is guided by clinical experience, because high-quality scientific data regarding the role of surgery in pelvic pain are sparse.…”
Section: Hormonal Medicationsmentioning
confidence: 99%
“…Unfortunately, hypoestrogenism induces many unpleasant side-effects such as hot flashes, uterine spotting and decrease in bone mineral density [21]. As mentioned earlier, aromatase inhibitors such as letrozole are being proposed as the new medical therapy for endometriosis [22]; however, well-designed clinical studies to test the efficacy of these drugs on an adequate sample size are still lacking [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is also concluded that the NPs are biocompatible and do not possess any significant toxicity in vitro (Figure 8). Moreover, Cur and Let are proven non-toxic drugs having undergone rigorous human clinical trials [9,22]. For selecting the ideal dose, 40 mg/kg of Let-Cur-NPs was administered in mice every day intra peritoneally and was studied for 7 consecutive days.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic study shows that the AIs, letrozole and anastrozole, are effective in treating pain symptoms; when withdrawn symptoms reappear, but they cannot be used for a long term therapy because of the adverse effects these compounds have on bone density (Ferrero et al, 2011). Endometriosis patients need chronic treatment, and this could be achieved combining AIs with a hormonal therapy to reduce the loss of bone density (Ferrero et al, 2011).…”
Section: Pge 2 Synthesis Inhibition and Pain Treatmentmentioning
confidence: 97%